STRUKTUR DAN SISTEM PEMBANGUNAN EKONOMI INDONESIA MASA ORDE BARU - Ida Bagus Gede Udiyana; I Gusti Gde Oka Pradnyana; Ni Nyoman Seri Astini (Forum Manajemen STIMI Handayani Denpasar, 2008)
This article analyse the structure and economic development system of indonesia of Orde baru period. The analysis is concerned at economic structure of indonesia, policy, failure and efficacy indonesian economic development of Orde period. This article represent the result of library research, therefore the data is secondary data in the form of books, journal and newspaper. This analysis is using the descriptivetechnique analysis by depicting all related variable with the purpose of writing, then studied in response to raised problems.